ARCHITECTURE BRANDING IN A LOCAL WISDOM BASED ON TOURISM DEVELOPMENT 4.0 IN BALI - Nimas Sekarlangit; L.V. Ratna Devi S. (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2019)
At present, the villages that have local wisdom in architecture Bali have undergone several changes. The change in the shape of the building caused because local people began to migrate to urban areas so that they had a changing lifestyle, and the difficulty of finding traditional materials. This problem generalizes the building style. However, tourism development in Bali is needed; therefore, branding can be carried out in architectural buildings which have local wisdom. Bali needs for the branding of architectural buildings containing speakable and writeable elements, a spirit of the brand, internal back-up, personality, and the story of glory with the power of local wisdom. Development of tourism based on the essence Hinduism, which was developed through the customer in the era of connectivity based on the principle of marketing 4.0. Marketing 4.0 is used to recognize the transitional role of traditional marketing and digital marketing in building customer involvement and advocacy. This study raises the question of architectural branding that has local wisdom in developing tourism 4.0. This study uses qualitative methods to look at comparison methods and marketing mixes. The output of this research is the traditional architecture of the Panglipuran and Tenganan traditional villages is a unique attraction for the village's tourism. It can increase tourist interest by adding an understanding of the local wisdom that underlies the building. So tourists will encourage other tourists to visit the traditional villages of Panglipuran and Tenganan.